Effects of lecithin as emulsifier on the performance of turkey poults - Halim, Siti Nurzihanum (2015)
An experiment was conducted to determine the effect of Lecithin as emulisifier on performance of poults. Thirty poults, one-day old of Local Bronze Turkey were randomly divide into three main groups of ten birds.The three group have divided into three subgroup each containing five birds.The poults were allocated into three treatment which are different percentage of Lecithin volume to be used in feeding with each treatment replicated two times. The experimental treatments were as follow; (T1) basal diet with 0% Lecithin as control; (T2) basal diet with 0.05% Lecithin and (T3) basal diet with 1.0% Lecithin. At the end of the experiment (84 d), poults in Treatment 3 showed that the highest body weight gain (p<0.05) compared to the others treatment. There is significant different of body weight gain in poults in Treatment 1 with Treatment 2 and 3. Poults fed with 0.05% (Treatment 2) and 1% (Treatment 3) of Lecithin are not significantly different and show the same positive highest bodyweight gain compared with poults fed with 0% of Lecithin in Treatment 1 and as control indicates that the lowest bodyweight gain. During week 12, statistical test showed there is significant different (P<0.05) among the treatments except week 5 indicated that there is no signficant different between Treatment 1,Treatment 2 and Treatment 3. Total feed intake was significantly affected by the different percentage of Lecithin as emulsifier in feeding diet. Turkey poults in Treatment 1 consumed most feed, 981g followed by birds in Treatment 2, 857.91g. Least feed consumed 811.91g by turkey poults was recorded for Treatment 3. Turkey poults in Treatment 3 had poor feed intake as compared to others treatments. Statistical test showed that there is significant different among these treatments. The various feeding diet with different percentage of Lecithin influnce on the efficiency of feed ultilization. The performance of turkey poults in Treatment 3, 1.046 of feed conversion ratio was encouraged in efficiency feed ultization and show good among others. Followed by Treatment 2, 1.243 feed conversion ratio and the poor of feed efficiency ultization showed in Treatment 1, 1.588 feed conversion ratio. As a conclusion that, feeding ration with Lecithin as emulsifier indicates that positive in result of feed conversion ration and good in performance of turkey poults compared than feeding ration without using the Lecithin as emulsifier. The result implied that treatment with soya-Lecithin as emulsifier had the highest growth performance compared with the treatment without added by soya-Lecithin.